2012
DOI: 10.1021/ct300111m
|View full text |Cite
|
Sign up to set email alerts
|

Improving Generalized Born Models by Exploiting Connections to Polarizable Continuum Models. I. An Improved Effective Coulomb Operator

Abstract: We investigate the generalized Born (GB) implicit solvation model in comparison with polarizable continuum models (PCMs). We show that the GB model is intimately connected to the conductor-like PCM (C-PCM), a method that is accurate for high-dielectric solvents but less so for weakly polar and nonpolar solvents. The formal connection between C-PCM and the GB model suggests that C-PCM calculations place a limit on the accuracy that one should expect from GB models but also demonstrates that comparison of GB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 64 publications
0
65
0
Order By: Relevance
“…A substantially different form of the GB kernel fijGB was recently proposed(59), based on a carefully examined connection between the GB and conductor-like polarizable continuum models(117): fij=rij+(1+1.028rij16RiRj)16 Noticeable improvements over the canonical GB in both accuracy and speed were reported(59), however the testing was so far limited to either the perfect or R6 effective Born radii.…”
Section: Polar Solvation: the Generalized Born Modelmentioning
confidence: 99%
“…A substantially different form of the GB kernel fijGB was recently proposed(59), based on a carefully examined connection between the GB and conductor-like polarizable continuum models(117): fij=rij+(1+1.028rij16RiRj)16 Noticeable improvements over the canonical GB in both accuracy and speed were reported(59), however the testing was so far limited to either the perfect or R6 effective Born radii.…”
Section: Polar Solvation: the Generalized Born Modelmentioning
confidence: 99%
“…Several computationally efficient adaptations/approximations of the general ASC formalism, notably many variants of Polarizable Continuum Model (PCM), e.g., COSMO, are widely used in computational chemistry to model solvation effects, see Ref for a comprehensive review. Some of these approximations are conceptually equivalent to the GB model …”
Section: Implicit Solvent Modelsmentioning
confidence: 99%
“…A great variety of flavors and implementations of the GB are available, several of which implemented in molecular modeling packages such as AMBER, CHARMM, GROMACS, NAMD, OpenMM, or TINKER . The specific choice depends on specific needs: a protein folding simulation may call for one flavor of the GB model, while a study of a protein in a membrane environment will need quite another .…”
Section: Implicit Solvent Modelsmentioning
confidence: 99%
“…There are good reasons to be skeptical of any "universal" definition based on a set of atomic radii. From a theoretical point of view, careful examination of the Born ion model 46 and the generalized Born (GB) formalism 152,153 suggests that the cavity radius is not strictly a property of the solute but ought to depend on the dielectric constant as well, and probably also on temperature 248 . A universal set of radii cannot capture changes in atomic size with respect to oxidation state, although empirical schemes have been suggested to modify the radii based on atomic charge 150,151 .…”
Section: Methodsmentioning
confidence: 99%
“…Beyond that, there is little theoretical justification for any of them, and no guarantee that small changes in the atomic radii will not have a significant impact on computed observables 113,149 . It has been suggested that the “optimal” atomic radius for a given atom likely ought to vary as a function of its partial atomic charge, 150,151 and probably as a function of the solvent's dielectric constant as well 94,132,152,153 . In quantum chemistry, the latter effect is generally neglected whereas the former is handled empirically, if at all.…”
Section: Continuum Electrostaticsmentioning
confidence: 99%